2002
DOI: 10.1074/jbc.m111799200
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Tail of α1,3-Galactosyltransferase Inhibits Golgi Localization of the Full-length Enzyme

Abstract: It is currently under debate whether the mechanism of Golgi retention of different glycosyltransferases is determined by sequences in the transmembrane, luminal, or cytoplasmic domains or a combination of these domains. We have shown that the cytoplasmic domains of ␣1,3-galactosyltransferase (GT) and ␣1,2-fucosyltransferase (FT) are involved in Golgi localization. Here we show that the cytoplasmic tails of GT and FT are sufficient to confer specific Golgi localization. Further, we show that the expression of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…Second, to detect the Golgi, we used the IB4 lectin, which binds to the Gal␣1,3Gal moiety of glycoconjugates. This linkage is produced by the ␣1-3-galactosyltransferase, which resides in the Golgi (43). As expected for a protein that is processed through the secretory pathway, the intracellular CD46 in transfected COS7 cells (Fig.…”
Section: Cd46mentioning
confidence: 77%
See 1 more Smart Citation
“…Second, to detect the Golgi, we used the IB4 lectin, which binds to the Gal␣1,3Gal moiety of glycoconjugates. This linkage is produced by the ␣1-3-galactosyltransferase, which resides in the Golgi (43). As expected for a protein that is processed through the secretory pathway, the intracellular CD46 in transfected COS7 cells (Fig.…”
Section: Cd46mentioning
confidence: 77%
“…After incubation with L-H cells, antibody localization was determined by either direct microscopy (if CD46-EGFP was used) or by fixation, permeabilization, and labeling with Alexa594-coupled antibody to mouse immunoglobulin. The Golgi was detected as previously described, by staining the Gal␣1,3Gal epitope after permeabilization with biotinylated IB4 followed by streptavidin Alexa594 (43). Immunofluorescence was analyzed using a Bio-Rad confocal scanning microscope (model MRC1000).…”
mentioning
confidence: 99%
“…We have also previously shown that the cytoplasmic tails of ␣1,3GT and ␣1,2fucosyltransferase (␣1,2FT) affect their subcellular localization (47,48). The ␣1,2FT is localized in an earlier subcompartment of the Golgi and is able to reduce Gal␣(1,3)Gal expression by competing for substrate (27).…”
Section: Previous Studies Of Ggta1mentioning
confidence: 99%
“…It has been shown that the cytoplasmic tails of the Golgiresident enzymes α1, 3-galactosyltransferase and α1, 2-fucosyltransferase are sufficient to confer their specific Golgi localization (Milland et al, 2002). Of the seven amino acids in the cytoplasmic tails of mouse HS6ST-1, -2, and -3, three residues (Asp3, Arg4 or Lys4, and Lys7) are conserved.…”
Section: Roles Of the Stem Domains In Golgi Localization Of Hs6stsmentioning
confidence: 99%